Echocardiography Screening for Latent Rheumatic Heart Disease: What Can We Do in Indonesia? - Soesanto, Amiliana M.; Suastika, Luh Oliva Saraswati (Frontiers in Surgery, 2020)
Rheumatic Heart Disease (RHD), a sequela of acute rheumatic fever (ARF), is a preventable disease but remains a significant health problem, especially in developing countries. It causes disability, poor quality of life, early mortality, and national economic burden. The World Heart Federation (WHF) aimed to achieve a 25% reduction in premature deaths from ARF and RHD among individuals aged <25 years by the year 2025. Primordial and primary prophylaxis of RHD is aimed to prevent the occurrence of ARF, while the goal of secondary and tertiary prophylaxis is to limit the progression and reduce the consequences of RHD. Early recognition of RHD is important for early prevention strategies to inhibit any progression to advanced stages. In 2012, WHF introduced the latest echocardiographic criteria to recognize the early stage of RHD. This includes the evaluation of pathological regurgitation jet and morphological features of RHD based on 2D, color, and spectral Doppler criteria. In remote areas, portable echocardiography is preferable for RHD screening. Previous portable devices were only capable of producing 2D and color images. Hence a simplified echocardiographic criterion without spectral Doppler evaluation is needed in selected areas. Indonesia is a developing country, an archipelago with a population of over 250 million. Currently, there is no data on the ARF incidence and RHD prevalence nationwide. The only data available is the number of patients in advanced stages who came to referral centers for further management. The screening program has to be introduced in Indonesia as a part of national RHD prevention.